Karakteristik Determinan Preeklamsia di RSUD dr. Soedono Madiun periode 1 Januari 2020 sampai dengan 31 Desember 2020 - HARIATI, FADILAMUNA; O. H. PRASETYADI, FRANS; PRANITASARI, NITA; EDY SUDIARTA, KETUT (Universitas Hang Tuah, 2025)
Abstract Background : Preeclampsia become one of the cases that causes maternal and perinatal morbidity and mortality. Morbidity and mortality occurs due to disorders in pregnancy (preeclampsia and eclampsia) by 14%. Preeclampsia is gestational hypertension characterized with increased blood pressure(2140/90mmHg), proteinuria(>300mg/24 hours), increased creatinine(>1.02mg/dL), and edema that can occur with age gestation >20 weeks. The purpose of this study is to determine the determinants which can cause preeclampsia in RSUD dr. Soedono Madiun, From January 1st2020 to December 31st2020. Methods : This type of research is descriptive research using a documentation study of patient medical record sheets at RSUD dr. Soedono Madiun from January 1st2020 to December 31st2020. The techniques sampling in this study is a purposive sampling technique. Univariate analysis is used to describe the characteristics of the variables that have been studied. Results : The case of preeclampsia in RSUD dr. Soedono as many as 67 cases. Most occurred in multigravida as many as 39cases (58.2%), at maternal age 20-35 as many as 48cases (71.6%), with the highest body mass index were obese or BMI more equal to 30 as many as 33cases (49.3%), hypertension as the most happened of maternal disease with 9cases (13.43%) and pregnancy disorders in 18cases (26.87%) with a long gestation interval. Conclusion : Preeclampsia is more common in multigravida pregnancies (2-4 weeks) at the age of the mother are 20-35 years with BMI more than 30 or obesity and mothers who have hypertension and long gestation interval. Keywords : Preeclampsia, Determinants